Main Areas of the Improvement of Investment Activity in the Construction Industry in the Republic of Kazakhstan - AITKHOZHINA, Alia; ALIYEV, Murat; AKIMOVA, Bibigul Zharmuhametovna; KAZHMUКHAMETOVA, Assem Arkhashevna; SAPARBAYEVA, Saule (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The present paper considers the modern approaches and developments on improving the management of investments in construction, inextricably intertwined with the enhancement of cooperation between the two major parties - designers and builders. The implementation of the project could involve several dozens of subcontractors in addition to the general contractor. It is possible to attract specialized construction organizations only when the nature and amount of special works in the construction of specific objects is known, and the final technical documentation is available.